2023
DOI: 10.1039/d2en00980c
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O@Co/N-doped carbon as antibacterial catalysts for oxygen reduction in microbial fuel cells

Abstract: Biofouling and sluggish kinetics on the cathode surface reduce the power generation of microbial fuel cells (MFCs). Herein, ZIF-derived Cu2O@Co/N-doped carbon (Cu2O@Co/NC) was used as an antibacterial oxygen reduction reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…The high resolution of N 1s could be deconvoluted into four characteristic peaks with four nitrogen species: pyridinic-N (398.6 eV), Co-N (399.1 eV), pyrrolic-N (399.8 eV) and graphitic-N (401.1 eV). 40 The peak of Co-N further confirmed that the bimetallic CoSn nanoparticles anchored on the carbon matrix by Co-N bonds. The relative amounts of pyridinic-N, graphitic-N, pyrrolic-N and Co-N were listed (Fig.…”
Section: Structural Informationmentioning
confidence: 70%
See 4 more Smart Citations
“…The high resolution of N 1s could be deconvoluted into four characteristic peaks with four nitrogen species: pyridinic-N (398.6 eV), Co-N (399.1 eV), pyrrolic-N (399.8 eV) and graphitic-N (401.1 eV). 40 The peak of Co-N further confirmed that the bimetallic CoSn nanoparticles anchored on the carbon matrix by Co-N bonds. The relative amounts of pyridinic-N, graphitic-N, pyrrolic-N and Co-N were listed (Fig.…”
Section: Structural Informationmentioning
confidence: 70%
“…The Co 2+ (781.6 and 796.6 eV), Co 0 (779.9 and 794.9 eV) and satellite peaks (787.3 and 802.3 eV) are the characteristic peaks of CoSn@NC. 40 A positive shift in the peak of Co 2+ revealed that Sn gained electrons from Co and modulated the electron redistribution between Co and Sn, endowing Co 2+ with a high oxidation state. The characteristic peaks of Sn 2+ (487.0 and 495.4 eV) and Sn 0 (486.5 and 494.9 eV) were identified in the Sn 3d spectrum of Sn@NC, while those of Sn 2+ (486.9 and 495.3 eV) and Sn 0 (486.4 and 494.8 eV) could be identified for CoSn@NC.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations